Cause and effect analysis of the Zimbabwean foreign exchange crisis:This paper was presented at ‘Business and Management Conference’ at the University of KwaZulu Natal, Durban, South Africa. on the 5th – 7th November 2009 - Nkomazana, Njabulo; Tambudzai, Zachary (Midlands State University, 2016)
Conference Paper